Equation "f(y)dx-zxdy-xylnydz=0" is integrable, if
"X\\cdot rotX=0\\\\\nX=(f(y),-zx,-xylny)"
Calculate "rotX" :
"rotX=\\nabla\\times X=\\begin{vmatrix}\n \\vec{i} & \\vec{j}&\\vec{k} \\\\\n \\frac{\\partial}{\\partial x} & \\frac{\\partial}{\\partial y}& \\frac{\\partial}{\\partial z}\\\\\nf(y)&-zx&-xylny\n\\end{vmatrix}=\\\\\n=\\vec{i}( \\frac{\\partial}{\\partial y}(-xylny)- \\frac{\\partial}{\\partial z}(-xz))-\\\\\n-\\vec{j}( \\frac{\\partial}{\\partial x}(-xylny)- \\frac{\\partial}{\\partial z}(f(y)))+\\\\\n+\\vec{k}( \\frac{\\partial}{\\partial x}(-zx)- \\frac{\\partial}{\\partial y}(f(y)))=\\\\\n=(-xlny)\\vec{i}+(ylny)\\vec{j}+(-z-f'(y))\\vec{k}"
Then
"X\\cdot rotX=-xlny\\cdot f(y)+xylnyf'(y)=0"
Thus "xlny\\cdot(yf'(y)-f(y))=0" , hence "yf'(y)-f(y)=0"
The solution of the last equation is determined by
"\\frac{df}{f}=\\frac{dy}{y}\\\\\nln|f(y)|=ln|y|+ln|A|\\\\\nf(y)=A\\cdot y"
where "A" is a real constant. Finally, equation takes the form
"Aydx-zxdy-xylnydz=0"
Using Natani’s method we firstly put "z=const" and solve the obtained equation
"Aydx=zxdy\\\\\na\\frac{dx}{x}=z\\frac{dy}{y}\\\\\nAlnx=zlny+F(z)"
Now we let "x=1" . Then equation takes the form
"-zdy-ylnydz=0"
and
"F(z)=-zlny"
Thus
"zdy+ylnydz=0\\\\\n\\frac{dy}{ylny}+\\frac{dz}{z}=0\\\\\nln|lny|=-ln|z|+ln|C|\\\\\nlny=\\frac{C}{z}"
Therefore,
"F(z)=-zlny=-z\\cdot\\frac{C}{z}=-C=K=const"
Finally,
"Alnx=zlny+K"
where "K" is an arbitrary real constant.
Comments
Leave a comment